Negative electrode for rechargeable lithium battery and rechargeable lithium battery including same
By designing a negative electrode active material layer including the first crystalline carbon layer, the Si-carbon composite silicon layer and the second crystalline carbon layer in the negative electrode of the rechargeable lithium battery, the lithium battery's lithium ion embedding and deintercalation process is solved. The problem of volume expansion improves cycle life and capacity retention.
Patent Information
- Application Number
- CN202410624058.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-16
- Filing Date
- 2024-05-20
- Publication Date
- 2025-02-21
AI Technical Summary
Existing rechargeable lithium batteries have volume expansion problems during lithium-ion embedding and deintercalation, which affects their cycle life and capacity retention.
A negative electrode for a rechargeable lithium battery is designed, including a current collector and an anode active material layer. The negative electrode active material layer consists of a first crystalline carbon layer, a silicon layer of Si-carbon composite and a second crystalline carbon layer, and the thickness of the silicon layer accounts for about 3% to 35% of the total thickness.
Through this design, the lithium battery expands less volume during charging and discharging, significantly improving cycle life and capacity retention.
Smart Images

Figure CN119495711A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure relate to a negative electrode for a rechargeable lithium battery and a rechargeable lithium battery including the same. Background Art
[0002] Recently, the rapid expansion of electronic devices using batteries (such as mobile phones, laptop computers and electric vehicles) has caused a dramatic increase in the desire and / or demand for rechargeable batteries with relatively high capacity and light weight. Therefore, research to improve the performance of rechargeable lithium batteries is being actively studied.
[0003] A rechargeable lithium battery includes a positive electrode and a negative electrode, each of which includes an active material capable of intercalating and deintercalating lithium ions, and an electrolyte. The rechargeable lithium battery generates electrical energy due to an oxidation-reduction reaction that occurs when lithium ions are intercalated and deintercalated into the positive electrode and the negative electrode. Summary of the invention
[0004] An aspect of one or more embodiments of the present disclosure is directed to a negative electrode for a rechargeable lithium battery having low volume expansion and excellent or suitable life cycle characteristics.
[0005] An aspect of one or more embodiments of the present disclosure is directed to a rechargeable lithium battery including a negative electrode.
[0006] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the disclosed presented embodiments.
[0007] According to one or more embodiments of the present disclosure, a negative electrode for a rechargeable lithium battery includes: a current collector; and a negative active material layer on at least one surface of the current collector, wherein the negative active material layer includes a first crystalline carbon layer in contact with the current collector, a silicon layer on the first crystalline carbon layer and including a Si-carbon composite, and a second crystalline carbon layer on the silicon layer, and the thickness of the silicon layer is about 3% to about 35% based on the total thickness of the negative active material layer.
[0008] According to one or more embodiments, a rechargeable lithium battery includes a negative electrode, a positive electrode including a positive active material, and a non-aqueous electrolyte.
[0009] One or more embodiments of the disclosure are included in the following detailed description.
[0010] A negative electrode for a rechargeable lithium battery according to one or more embodiments may have relatively low volume expansion during charge and discharge and excellent or suitable life cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a schematic diagram illustrating a negative electrode for a rechargeable lithium battery according to one or more embodiments of the present disclosure.
[0012] Figures 2 to 5 are schematic diagrams each showing a rechargeable lithium battery according to one or more embodiments of the present disclosure. DETAILED DESCRIPTION
[0013] The present disclosure can be modified in many alternative forms, and therefore specific embodiments will be shown in the drawings and described in more detail. However, it will be understood that this is not intended to limit the present disclosure to the particular form disclosed, but on the contrary, it is intended to cover all modifications, equivalents and substitutes falling within the spirit and scope of the present disclosure.
[0014] Hereinafter, example embodiments will be described in more detail with reference to the accompanying drawings. However, the present disclosure may be implemented in various different forms and should not be construed as being limited to the embodiments shown herein. On the contrary, these embodiments are provided as examples so that the present disclosure will be thorough and complete, and will fully convey the aspects and features of the present disclosure to those skilled in the art. Therefore, processes, elements, and techniques that are not necessary for a person of ordinary skill in the art to fully understand the aspects and features of the present disclosure may not be described.
[0015] As used herein, and when no definition is otherwise provided, it will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, the element can be directly on the other element or one or more intervening elements may also be present. Additionally, it will be understood that when an element or layer is referred to as being "between" two elements or layers, the layer can be the only element or layer between the two elements or layers, or one or more intervening elements or layers may also be present.
[0016] As used herein, the singular forms "a", "an", and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. Unless otherwise specified, "A or B" may mean "including A, including B, or including A and B". Unless otherwise apparent from the disclosure, postpositional phrases such as "at least one of", "a plurality of", "one of", and others, when following a list of elements, should be understood to include the disjunctive conjunction when written as a list of conjunctions, and vice versa. For example, the expressions "at least one of a, b or c", "at least one of a, b and / or c", "one selected from the group consisting of a, b and c", "at least one selected from a, b and c", "at least one from a, b and c", "one from a, b and c", and "at least one from a to c" mean only a, only b, only c, both a and b, both a and c, both b and c, all of a, b and c, or variations thereof.
[0017] As used herein, the term "combination thereof" may include mixtures, laminates, composites, copolymers, alloys, blends, and / or reactants of the constituent parts.
[0018] In the present disclosure, when the particle is spherical, "diameter" means particle diameter or average particle diameter, and when the particle is non-spherical, "diameter" means major axis length or average major axis length. This particle diameter represents average particle diameter (D50), wherein D50 refers to the average diameter (average size) of the cumulative volume of particles corresponding to 50 volume % (vol%) in particle size distribution (e.g., cumulative distribution), and refers to the value corresponding to 50% of the particle diameter from the smallest particle when the total number of particles in the distribution curve accumulated in the order of minimum particle diameter to maximum particle diameter is 100%. Average particle diameter (D50) can be measured by a generally available and / or suitable method (e.g., by a particle size analyzer or by a transmission electron microscope image or a scanning electron microscope image) by those skilled in the art. In one or more embodiments, a dynamic light scattering measurement device is used to perform data analysis, and the number of particles is counted for each particle size range, whereby the average particle diameter (D50) value can be easily obtained by calculation. Particle diameter can be measured by a laser diffraction method. Laser diffraction can be obtained by dispersing the particles to be measured in a dispersion solvent and introducing them into a commercially available laser diffraction particle measuring device (for example, MT 3000 available from Microtrac Co., Ltd.), irradiating ultrasonic waves of about 28 kHz at a power of 60 W, and calculating the average particle size (D50) in the 50% standard of the particle distribution in the measuring device.
[0019] It will also be understood that when the terms "includes," "comprising," and "having" and variations thereof are used in this specification, they indicate the presence of the stated features, integers (integrity), steps, operations, elements (components), and / or components, but do not preclude the presence or addition of one or more other features, integers (integrity), steps, operations, elements (components), components, and / or groups thereof. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0020] Unless otherwise noted, the same reference numerals refer to the same elements throughout the drawings and written description, and thus, a repeated description thereof may not be provided. In the drawings, the relative sizes of elements, layers, and regions may be exaggerated for clarity.
[0021] It will be understood that, although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the spirit and scope of the present disclosure, the first element, first component, first region, first layer or first part described below may be named as the second element, second component, second region, second layer or second part.
[0022] For ease of explanation, spatially relative terms such as "top", "bottom", etc. may be used herein to describe the relationship between one element or feature and another (or some) elements or features as shown in the figure. It will be understood that, in addition to covering the orientation depicted in the figure, spatially relative terms are also intended to cover different orientations of the device in use or operation. For example, if the device in the figure is turned over, the element or feature described as "on the "top" of other elements or features will be oriented to be on the "bottom" of the other elements or features. Therefore, the example term "top" can cover both upper and lower orientations. The device can be oriented otherwise (e.g., rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein should be interpreted accordingly.
[0023] A negative electrode for a rechargeable lithium battery according to one or more embodiments includes a current collector and a negative active material layer including (eg, consisting of) three layers: a first active material layer, a second active material layer, and a third active material layer.
[0024] The negative electrode active material layer according to one or more embodiments includes a three-layer structure (e.g., composed of a three-layer structure) including a first layer in contact with a current collector, a third layer on a surface, and a second layer between the first layer and the third layer. The first layer and the third layer may be a first crystalline carbon layer and a second crystalline carbon layer in which the negative electrode active material is crystalline carbon, and the second layer may be a silicon layer including a Si-carbon composite as an active material.
[0025] If reference Figure 1 Such a negative electrode is shown in more detail (for example, when referring to Figure 1 When such a negative electrode is shown in more detail, the negative electrode 1 according to one or more embodiments includes a silicon layer 7 between a first crystalline carbon layer 5 and a second crystalline carbon layer 9. For example, the silicon layer 7 is included in the negative electrode as an intermediate layer, the first crystalline carbon layer 5 is included in direct contact with the current collector 3, and the second crystalline carbon layer 9 is positioned on a surface (for example, a surface of the negative electrode 1 opposite to the current collector 3).
[0026] In one or more embodiments, the first crystalline carbon layer and the second crystalline carbon layer are active material layers in which the active material is crystalline carbon.
[0027] The crystalline carbon may be graphite such as natural graphite and / or artificial graphite in the form of no definite shape, flake, flaky, spherical or fibrous shapes.
[0028] In one or more embodiments, the first crystalline carbon and the second crystalline carbon may be artificial graphite, natural graphite or any suitable mixture thereof. According to one or more embodiments, the first crystalline carbon and the second crystalline carbon may be any suitable mixture of artificial graphite and natural graphite.
[0029] In one or more embodiments, the silicon layer may include a Si-carbon composite as an active material and may further include crystalline carbon.
[0030] Including a Si-carbon composite in the silicon layer can increase the capacity, and when the Si-carbon composite is positioned as an intermediate layer, the first active material layer and the third active material layer positioned on the top and bottom, respectively, can absorb the volume expansion of Si that occurs during charging and discharging, thereby maintaining the entire volume of the negative electrode active material layer. For example, this volume expansion suppression effect can be more effectively achieved in crystalline carbon (which has a low hardness compared to amorphous carbon or a mixture of amorphous carbon and crystalline carbon) as the active material of the first active material layer and the third active material layer, thereby having the benefit and / or advantage of elasticity.
[0031] In the negative electrode according to one or more embodiments, the thickness percentage of the silicon layer may be about 3% to about 35% based on the total thickness of the negative electrode active material layer. In one or more embodiments, the thickness percentage of the silicon layer may be about 5% to about 33% or about 12% to about 30% based on the total thickness of the negative electrode active material layer.
[0032] If the thickness of the silicon layer is within the above range (for example, when the thickness of the silicon layer is within the above range), a relatively high capacity can be achieved due to the inclusion of the Si-C composite, and the volume expansion of the silicon layer can be effectively (or substantially effectively) absorbed by the first crystalline carbon layer and the second crystalline carbon layer serving as an effective (or substantially effective) buffer. Therefore, the volume expansion of the electrode can be effectively suppressed or reduced, thereby improving the cycle life characteristics. If the thickness % of the silicon layer is less than about 3% (for example, when the thickness % of the silicon layer is less than about 3%), the capacity of the rechargeable lithium battery may be reduced. If the thickness % of the silicon layer is greater than about 35% (for example, when the thickness % of the silicon layer is greater than about 35%), the thickness of the first crystalline carbon layer and the second crystalline carbon layer is relatively thin and may be insufficient to absorb the volume expansion.
[0033] If the silicon layer is positioned in contact with the current collector (for example, when the silicon layer is positioned in contact with the current collector), for example, if the silicon layer corresponds to the first layer (for example, when the silicon layer corresponds to the first layer), then the effect of suppressing volume expansion can be obtained, but the resistance will increase due to the direct contact between the current collector and the silicon. If the silicon layer is positioned on the surface of the negative electrode (for example, the surface of the negative electrode opposite to the surface in contact with the current collector) (for example, when the silicon layer is positioned on the surface of the negative electrode (for example, the surface of the negative electrode opposite to the surface in contact with the current collector)), for example, the silicon layer corresponds to the third layer, then the position of the silicon layer is on the crystalline carbon layer that acts as a buffer for absorbing volume expansion (for example, not between the crystalline carbon layers), so the effect of suppressing volume expansion will be insufficient.
[0034] In one or more embodiments, the thickness of the silicon layer may be about 10 μm to 85 μm, about 15 μm to about 70 μm, about 15 μm to about 50 μm, or about 20 μm to 50 μm.
[0035] The thickness of the first crystalline carbon layer 5 may be about 10 μm to about 120 μm, about 20 μm to about 100 μm, or about 30 μm to 80 μm.
[0036] The thickness of the second crystalline carbon layer 9 may be about 10 μm to about 120 μm, about 20 μm to about 100 μm, or about 30 μm to 80 μm.
[0037] While the silicon layer 7, the first crystalline carbon layer 5 and the second crystalline carbon layer 9 satisfy the thickness %, for example, if the thickness of each layer satisfies the above range (for example, when the thickness of each layer satisfies the above range), then the buffering effect of absorbing the expansion of the silicon layer by the carbon layer can be more fully realized, thereby being more effectively controlled or selected.
[0038] In the negative electrode according to one or more embodiments, the silicon-carbon composite included in the second active material layer (e.g., silicon layer 7) may include silicon particles and carbon-based materials. The silicon particles may be silicon nanoparticles. The carbon-based material may be amorphous carbon, or may be amorphous carbon and crystalline carbon.
[0039] In one or more embodiments, the silicon-carbon composite may include silicon nanoparticles and an amorphous carbon coating on surfaces of the silicon nanoparticles.
[0040] The silicon-carbon composite may also include an agglomeration product in which silicon nanoparticles are agglomerated, and an amorphous carbon coating is on the surface of the agglomeration product. That is, the Si-carbon composite may include secondary particles in which silicon primary particles (e.g., silicon nanoparticles) are agglomerated, and amorphous carbon may be on the primary particles and the secondary particles. For example, the Si-carbon composite may be in the form of secondary particles in which silicon primary particles are agglomerated (e.g., in each secondary particle).
[0041] The silicon nanoparticles may have a particle size (e.g., average particle size) of about 10 nm to about 1000 nm, and according to one or more embodiments, may be about 10 nm to 200 nm or about 20 nm to about 150 nm. If the average particle size of the silicon nanoparticles is within the above range (e.g., when the average particle size of the silicon nanoparticles is within the above range), excessive volume expansion caused during charging and discharging may be suppressed or reduced, and damage to the conductive path caused by the breakage of the particles may be prevented or reduced.
[0042] In the amorphous carbon coating, the amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbide, sintered coke, or any suitable combination thereof. The thickness of the amorphous carbon coating may be about 1 nm to about 2 μm, about 1 nm to about 500 nm, about 10 nm to about 300 nm, or about 20 nm to about 200 nm. If the thickness of the amorphous carbon coating is within the above range (e.g., when the thickness of the amorphous carbon coating is within the above range), the volume expansion of silicon can be better suppressed or reduced during charge and discharge.
[0043] The silicon-carbon composite may further include crystalline carbon. If the silicon-carbon composite further includes crystalline carbon (for example, when the silicon-carbon composite further includes crystalline carbon), it may include an agglomeration product in which silicon nanoparticles and crystalline carbon are agglomerated and an amorphous carbon coating on the surface of the agglomeration product.
[0044] The crystalline carbon may include natural graphite or artificial graphite in the form of no definite shape, flake, flaky, spherical or fibrous shapes, or any suitable combination thereof.
[0045] If the silicon-carbon composite includes silicon nanoparticles and an amorphous carbon coating (for example, when the silicon-carbon composite includes silicon nanoparticles and an amorphous carbon coating), the amount of the silicon nanoparticles may be about 30 wt % to about 70 wt % or about 40 wt % to about 65 wt % based on the total amount 100 wt % of the silicon-carbon composite. The amount of the amorphous carbon coating may be about 30 wt % to about 70 wt % or about 35 wt % to about 60 wt % based on the total amount 100 wt % of the silicon-carbon composite.
[0046] If the silicon-carbon composite further includes crystalline carbon (for example, when the silicon-carbon composite further includes crystalline carbon), then the amount of the silicon nanoparticles may be about 20 wt% to about 70 wt% or about 25 wt% to about 65 wt% based on the total amount 100 wt% of the silicon-carbon composite. The amount of amorphous carbon may be about 25 wt% to about 70 wt% or about 25 wt% to about 60 wt% based on the total amount 100 wt% of the silicon-carbon composite, and the amount of crystalline carbon may be about 1 wt% to about 20 wt% or about 5 wt% to about 15 wt%.
[0047] The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbide, sintered coke, or any suitable combination thereof.
[0048] In one or more embodiments, the second active material layer (e.g., silicon layer 7) may further include crystalline carbon. For example, the second active material layer may include a silicon-carbon composite as a negative electrode active material together with crystalline carbon. The mixing ratio of the silicon-carbon composite and the crystalline carbon may be about 9:91 to about 60:40 by weight, about 9:91 to about 50:50 by weight, about 9:91 to about 95:5 by weight, about 9:91 to about 90:10 by weight, about 80:20 to about 95:5 by weight, or about 90:10 to about 95:5 by weight. If the mixing ratio of the silicon-carbon composite and the crystalline carbon is within the above range (e.g., when the mixing ratio of the silicon-carbon composite and the crystalline carbon is within the above range), a higher capacity can be obtained.
[0049] The first active material layer (eg, first crystalline carbon layer 5 ), the second active material layer (eg, silicon layer 7 ), and the third active material layer (eg, second crystalline carbon layer 9 ) may include a binder, respectively, and may further include a conductive material.
[0050] In the first active material layer, the second active material layer, and the third active material layer, an amount of the negative electrode active material in each may be about 90 wt % to about 99 wt % or about 94 wt % to about 99 wt %.
[0051] In the first active material layer, the second active material layer, and the third active material layer, the amount of the binder in each may be about 0.5 wt % to about 5 wt % or about 0.5 wt % to about 3 wt % based on the total amount 100 wt % of each corresponding active material layer. In the first active material layer, the second active material layer, and the third active material layer, the amount of the conductive material in each may be about 0.5 wt % to about 5 wt % or about 0.5 wt % to about 3 wt % based on the total amount 100 wt % of each corresponding active material layer.
[0052] The binder may be used to attach the negative electrode active material particles to each other and also to attach the negative electrode active material to the current collector. The binder may include a non-aqueous binder, an aqueous binder, or any suitable combination thereof.
[0053] The non-aqueous binder may be polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or any suitable combination thereof.
[0054] The aqueous binder can be styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(methyl)nitrile, ethylene-propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol or any suitable combination thereof.
[0055] The negative electrode binder may include a cellulose compound, or may be a cellulose compound together with an aqueous binder. The cellulose compound may include one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and an alkali metal salt thereof. The alkali metal may be Na, K or Li. The cellulose compound may be used as a binder and may impart viscosity to act as a thickener. Therefore, the amount of the cellulose compound may be appropriately adjusted within the amount of the binder, for example, based on 100 parts by weight of the negative electrode active material, the amount of the cellulose compound may be from about 0.1 parts by weight to about 3 parts by weight.
[0056] The dry binder (eg, non-aqueous binder) may be a polymer that can be fibrous. For example, the dry binder may be polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or any suitable combination thereof.
[0057] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may be: a carbon-based material such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and / or carbon fiber, etc.; a metal-based material including metal powder or metal fiber of copper, nickel, aluminum, and / or silver, etc.; a conductive polymer such as a polyphenylene derivative; or any suitable combination thereof.
[0058] The current collector may include one of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and / or any suitable combination thereof (eg, one selected from the foregoing), but the present disclosure is not limited thereto.
[0059] Rechargeable lithium battery
[0060] One or more embodiments of the present disclosure provide a rechargeable lithium battery including a negative electrode according to one or more embodiments, a positive electrode, and an electrolyte.
[0061] Positive electrode
[0062] The positive electrode may include a current collector and a positive active material on the current collector.
[0063] The positive electrode active material may include a positive electrode active material and further include a binder and / or a conductive material. For example, the positive electrode may further include an additive that may serve as a sacrificial positive electrode.
[0064] The positive electrode active material may include a compound capable of inserting and extracting lithium (lithiated inserting compound). In one or more embodiments, at least one of a composite oxide of lithium and a metal (e.g., a metal selected therefrom) of cobalt, manganese, nickel, and / or any suitable combination thereof may be used.
[0065] The composite oxide may be a lithium transition metal composite oxide. Examples of the composite oxide may include lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate compounds, cobalt-free nickel manganese-based oxides, or any suitable combination thereof.
[0066] As an example, the following compounds represented by any one of the following chemical formulas may be used: Li a A 1-b X b O 2- c D c(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Mn 2-b X b About 4-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Ni 1-b-c Co b X c About 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b- c Mn b X c About 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni b Co c L 1 d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0≤e≤0.1);Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-b G b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn2G b O4(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-g G g PO4(0.90≤a≤1.8,0≤g≤0.5);Li (3-f) Fe2(PO4)3(0≤f≤2);Li a FePO4(0.90≤a≤1.8).
[0067] In the above chemical formula, A is Ni, Co, Mn or any suitable combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or any suitable combination thereof; D is O, F, S, P or any suitable combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or any suitable combination thereof; and L 1 is Mn, Al or any suitable combination thereof.
[0068] The positive electrode active material may be, for example, a high nickel positive electrode active material having a nickel content (e.g., amount) of about 80 mol%, about 85 mol%, about 90 mol%, about 91 mol%, about 94 mol%, and about 99 mol% or less based on 100 mol% of the metal other than lithium in the lithium transition metal composite oxide. The high nickel positive electrode active material may be able to achieve high capacity and may be applied to high capacity and high density rechargeable lithium batteries.
[0069] In the positive electrode, the amount of the positive active material may be about 90 wt % to about 98 wt % based on the total weight of the positive active material layer, and the amount of the binder and the conductive material may each be about 0.5 wt % to about 5 wt % based on 100 wt % of the positive active material layer.
[0070] The binder is used to attach the positive electrode active material particles to each other and also to attach the positive electrode active material to the current collector.
[0071] Examples of binders may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylic esterified styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin and / or nylon as non-limiting examples.
[0072] Conductive materials may be used to impart conductivity (e.g., electrical conductivity) to electrodes. Any material that does not cause chemical changes (e.g., does not cause undesirable chemical changes in a rechargeable lithium battery) and conducts electrons may be used in the battery. Examples of conductive materials may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and / or carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, etc. in the form of metal powders or metal fibers; conductive polymers such as polyphenylene derivatives; or any suitable mixture thereof.
[0073] Al may be used as a current collector, but the present disclosure is not limited thereto.
[0074] Electrolyte
[0075] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0076] The non-aqueous organic solvent may be used as a medium for transporting ions participating in the electrochemical reaction of the battery.
[0077] The non-aqueous organic solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent or any suitable combination thereof.
[0078] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC) and / or butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonolactone, valerolactone and / or caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran and / or tetrahydrofuran, etc. Ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol and / or isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN (wherein R is a C2 to C20 straight chain, branched or cyclic hydrocarbon, a double bond, an aromatic ring or an ether bond)), amides (such as dimethylformamide), dioxolanes (such as 1,3-dioxolane and / or 1,4-dioxolane, etc.) and / or cyclopentane, etc.
[0079] The nonaqueous organic solvent may be used alone or in combination of two or more.
[0080] In one or more embodiments, if a carbonate solvent is used (eg, when a carbonate solvent is used), cyclic carbonate and chain carbonate may be mixed and used, and the cyclic carbonate and chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0081] Lithium salts dissolved in organic solvents supply lithium ions in the battery, enable basic operations of rechargeable lithium batteries, and improve the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers from 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluoro(oxalato)phosphate (LiDFBP) and / or lithium bis(oxalato)borate (LiBOB) (e.g., at least one selected from the foregoing substances).
[0082] Diaphragm
[0083] Depending on the type or kind of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers thereof and / or a mixed multilayer film (such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and / or a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0084] The separator may include a porous substrate and a coating including an organic material, an inorganic material, or any suitable combination thereof on one or both (eg, opposing) surfaces of the porous substrate.
[0085] The porous substrate can be a polymer film formed from any one of polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (TEFLON) and polytetrafluoroethylene (for example, any one selected from the foregoing substances), or a copolymer of two or more of the foregoing substances or any suitable mixture.
[0086] The organic material may include a polyvinylidene fluoride-based polymer or a (meth)acrylic polymer.
[0087] The inorganic material may include inorganic particles of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite and / or any suitable combination thereof (e.g., selected from the foregoing), but the present disclosure is not limited thereto.
[0088] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.
[0089] Rechargeable lithium batteries may be classified into cylindrical, prismatic, pouch or coin type or kind batteries and / or the like according to their shapes. Figures 2 to 5 is a schematic diagram illustrating a rechargeable lithium battery according to an embodiment of the present disclosure. Figure 2 A cylindrical battery is shown, Figure 3 A prismatic cell is shown, Figure 4 and Figure 5 A pouch-type or bag-style battery is shown. Figures 2 to 5 , the rechargeable lithium battery 100 may include an electrode assembly 40 and a case 50 including the electrode assembly 40 therein, the electrode assembly 40 including a separator 30 between a positive electrode 10 and a negative electrode 20. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte. For example, Figure 2 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 3 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 4 and Figure 5 As shown in , the rechargeable lithium battery 100 may include electrode tabs 70 serving as an electrical path for introducing current formed in the electrode assembly 40 to the outside, and the electrode tabs 70 may be, for example, a positive electrode tab 71 and a negative electrode tab 72 .
[0090] The following examples and comparative examples are provided to highlight the characteristics of one or more embodiments, but it will be understood that the examples and comparative examples are not interpreted as limiting the scope of the present disclosure, and the comparative examples are not interpreted as being outside the scope of the embodiments. In addition, it will be understood that the embodiments are not limited to the specific details described in the examples and comparative examples. The following examples are merely example embodiments, and the present disclosure is not limited to the following examples.
[0091] Example 1
[0092] 97.46 wt % of a mixture of natural graphite and artificial graphite (the mixing ratio of natural graphite and artificial graphite is 50:50 by weight), 1.7 wt % of styrene-butadiene rubber, 0.8 wt % of carboxymethyl cellulose and 0.04 wt % of single-walled carbon nanotubes (SWCNTs) are mixed in an aqueous solvent to prepare a first crystalline carbon layer slurry.
[0093] 80 wt % of silicon-carbon composite, 17.46 wt % of artificial graphite, 1.7 wt % of styrene-butadiene rubber, 0.8 wt % of carboxymethyl cellulose, and 0.04 wt % of SWCNT were mixed in a water solvent to prepare a slurry for a silicon layer.
[0094] A silicon-carbon composite including an agglomerated product in which silicon nanoparticles having an average particle size (D50) of 100 nm and soft carbon and a soft carbon coating on the agglomerated product was used. Based on the total weight of the silicon-carbon composite, the amount of the silicon nanoparticles was 54 wt % and the amount of the soft carbon was 46 wt %, and the thickness of the soft carbon coating was 100 nm.
[0095] 97.46 wt % of a mixture of natural graphite and artificial graphite (the mixing ratio of natural graphite and artificial graphite is 50:50 by weight), 1.7 wt % of styrene-butadiene rubber, 0.8 wt % of carboxymethyl cellulose and 0.04 wt % of SWCNT were mixed in a water solvent to prepare a second crystalline carbon layer slurry.
[0096] On a Cu foil current collector, a first crystalline carbon layer slurry, a silicon layer slurry, and a second crystalline carbon layer slurry were sequentially coated and dried, and then pressed to prepare a negative electrode in which a first crystalline carbon layer (thickness: 42.5 μm), a silicon layer (thickness: 15 μm), and a second crystalline carbon layer (thickness: 42.5 μm) were sequentially formed on the current collector.
[0097] 97.8wt% LiNi 0.91 Co 0.07 Mn 0.01 Al 0.01 The O2 positive electrode active material, 1.1 wt% of a carbon conductive material and 1.1 wt% of a polyvinylidene fluoride binder were mixed in an N-methylpyrrolidone solvent to prepare a positive electrode active material layer slurry.
[0098] The positive active material layer slurry was coated on an Al foil current collector, dried and pressed to prepare a positive electrode.
[0099] A full-cell was fabricated using a negative electrode, a positive electrode and an electrolyte. The electrolyte was prepared by dissolving 1.5 M LiPF6 in ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate (volume ratio of 20:10:70).
[0100] Example 2
[0101] The first crystalline carbon layer slurry prepared in Example 1, the silicon layer slurry prepared in Example 1, and the second crystalline carbon layer slurry prepared in Example 1 were used to prepare a negative electrode having a first crystalline carbon layer having a thickness of 15 μm, a silicon layer having a thickness of 15 μm, and a second crystalline carbon layer having a thickness of 70 μm on a current collector through substantially the same steps as in Example 1.
[0102] A full cell was manufactured through substantially the same steps as in Example 1 using the negative electrode.
[0103] Example 3
[0104] The first crystalline carbon layer slurry prepared in Example 1, the silicon layer slurry prepared in Example 1, and the second crystalline carbon layer slurry prepared in Example 1 were used to prepare a negative electrode having a first crystalline carbon layer with a thickness of 70 μm, a silicon layer with a thickness of 15 μm, and a second crystalline carbon layer with a thickness of 15 μm on a current collector through substantially the same steps as in Example 1.
[0105] A full battery cell was manufactured through substantially the same steps as in Example 1 using the negative electrode.
[0106] Comparative Example 1
[0107] The silicon layer slurry prepared in Example 1 was coated on a Cu foil current collector, dried, and pressed to prepare a negative electrode including a silicon layer having a thickness of 100 μm.
[0108] A full battery cell was manufactured through substantially the same steps as in Example 1 using the negative electrode.
[0109] Comparative Example 2
[0110] The first crystalline carbon layer slurry prepared in Example 1, the second crystalline carbon layer slurry prepared in Example 1, and the silicon layer slurry prepared in Example 1 were sequentially coated on a Cu foil current collector, dried, and then pressed to prepare a negative electrode having a first crystalline carbon layer (thickness: 42.5 μm), a second crystalline carbon layer (thickness: 42.5 μm), and a silicon layer (thickness: 15 μm) sequentially formed on the current collector.
[0111] A full battery cell was manufactured through substantially the same steps as in Example 1 using the negative electrode.
[0112] Comparison Example 3
[0113] The silicon layer slurry prepared in Example 1, the first crystalline carbon layer slurry prepared in Example 1, and the second crystalline carbon layer slurry prepared in Example 1 were sequentially coated on a Cu foil current collector, dried, and then pressed to prepare a negative electrode having a silicon layer (thickness: 15 μm), a first crystalline carbon layer (thickness: 42.5 μm), and a second crystalline carbon layer (thickness: 42.5 μm) sequentially formed on the current collector.
[0114] A full battery cell was manufactured through substantially the same steps as in Example 1 using the negative electrode.
[0115] Comparison Example 4
[0116] The first crystalline carbon layer slurry prepared in Example 1, the silicon layer slurry prepared in Example 1, and the second crystalline carbon layer slurry prepared in Example 1 were used to prepare a negative electrode having a first crystalline carbon layer (thickness: 45 μm), a silicon layer (thickness: 10 μm), and a second crystalline carbon layer (thickness: 45 μm) sequentially formed on a current collector.
[0117] A full battery cell was manufactured through substantially the same steps as in Example 1 using the negative electrode.
[0118] Comparative Example 5
[0119] The first crystalline carbon layer slurry prepared in Example 1, the silicon layer slurry prepared in Example 1, and the second crystalline carbon layer slurry prepared in Example 1 were used to prepare a negative electrode having a first crystalline carbon layer (thickness: 32 μm), a silicon layer (thickness: 36 μm), and a second crystalline carbon layer (thickness: 32 μm) sequentially formed on a current collector.
[0120] A full battery cell was manufactured through substantially the same steps as in Example 1 using the negative electrode.
[0121] Experimental Example 1) Evaluation of room temperature cycle life
[0122] The full battery cells according to Examples 1 to 3 and Comparative Examples 1 to 5 were charged and discharged for 70 cycles under the following conditions at room temperature (25°C, RT). The ratio of the discharge capacity at each cycle to the discharge capacity at the first cycle was measured. The results are shown in Table 1.
[0123] Charging: Constant current / constant voltage, 0.5C, 4.25V, 0.05C cut-off, pause 10 minutes
[0124] Discharge: Constant current 0.5C, 2.8V cut-off, pause 10 minutes
[0125] Table 1
[0126] Thickness of silicon layer % Capacity retention rate (%) Example 1 15 85 Example 2 15 83 Example 3 15 82 Comparative Example 1 - 80 Comparative Example 2 15 70 Comparison Example 3 15 78 Comparison Example 4 10 80 Comparative Example 5 36 75
[0127] As shown in Table 1, the battery cells of Examples 1 to 3 in which the silicon layer was positioned as an intermediate layer (eg, in the center) and the thickness % of the silicon layer based on the total thickness of the negative active material layer was 15% exhibited excellent or suitable capacity retention rates.
[0128] However, if the silicon layer is not included (Comparative Example 1), or the silicon layer is positioned on the top (Comparative Example 2) or the bottom (Comparative Example 3) (for example, when the silicon layer is not included (Comparative Example 1), or the silicon layer is positioned on the top (Comparative Example 2) or the bottom (Comparative Example 3)), the capacity retention rate is significantly deteriorated. It was found that even if the silicon layer is positioned in the middle (for example, in the center), if the thickness % of the silicon layer is too small (Comparative Example 4) or too large (Comparative Example 5) (for example, when the thickness % of the silicon layer is too small (Comparative Example 4) or too large (Comparative Example 5)), the capacity retention rate is also deteriorated.
[0129] For example, Comparative Examples 1 to 5 showed a capacity retention rate of 80% or less, which is not suitable for use as a battery. Therefore, the battery cells of Comparative Examples 1 to 5 are not suitable for application as practical battery cells.
[0130] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those of ordinary skill in the art to which the present disclosure belongs. It will also be understood that terms (such as those defined in general dictionaries) should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and / or in this specification, and should not be interpreted in an idealized or overly formal sense, unless explicitly defined as such herein.
[0131] As used herein, the terms "substantially," "approximately," "approximately," and similar terms are used as terms of approximation rather than terms of degree, and are intended to account for the inherent deviations in measured or calculated values that one of ordinary skill in the art would recognize. As used herein, "approximately" includes the stated value and means within the acceptable range of deviation of the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "approximately" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, ±5% of the stated value.
[0132] In addition, any numerical range listed here is intended to include all sub-ranges of the same numerical precision contained in the listed range. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges between the listed minimum value 1.0 and the listed maximum value 10.0 (and including the listed minimum value 1.0 and the listed maximum value 10.0), that is, having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit listed here is intended to include all lower numerical limits contained therein, and any minimum numerical limit listed in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to modify this specification (including claims) to explicitly list any sub-ranges contained in the range explicitly listed here.
[0133] Furthermore, the use of “may” when describing embodiments of the present disclosure refers to “one or more embodiments of the present disclosure.”
[0134] The portable device, vehicle and / or battery (e.g., battery controller) and / or any other related device or component according to the embodiments of the present disclosure described herein can be implemented using any suitable hardware, firmware (e.g., application specific integrated circuit), software, or a combination of software, firmware and hardware. For example, the various components of the device can be formed on an integrated circuit (IC) chip or on a separate IC chip. In addition, the various components of the device can be implemented on a flexible printed circuit film, a carrier package (TCP), a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device can be processes or threads running on one or more processors in one or more computing devices, and the one or more computing devices execute computer program instructions and interact with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which can be implemented in a computer device using a standard memory device such as a random access memory (RAM) as an example. The computer program instructions can also be stored in other non-temporary computer-readable media such as CD-ROMs, flash drives, etc. as examples. In addition, those skilled in the art should recognize that the functionality of various computing devices may be combined or integrated into a single computing device, or the functionality of a particular computing device may be distributed to one or more other computing devices without departing from the scope of the embodiments of the present disclosure.
[0135] Although the embodiments of the present disclosure have been described, it will be understood that the present disclosure should not be limited to these embodiments, but one or more suitable modifications and variations may be made by one of ordinary skill in the art within the spirit and scope of the present disclosure as defined by the appended claims and their equivalents.
Claims
1. A negative electrode for a rechargeable lithium battery, the negative electrode comprising: current collector; as well as A negative electrode active material layer, on at least one surface of the current collector, Wherein, the negative electrode active material layer comprises: a first crystalline carbon layer in contact with the current collector; a silicon layer on the first crystalline carbon layer and comprising a Si-carbon composite; and a second crystalline carbon layer on the silicon layer, and Wherein, based on the total thickness of the negative electrode active material layer, the thickness of the silicon layer is 3% to 35%.
2. The negative electrode according to claim 1, wherein The thickness of the silicon layer is 5% to 33% based on the total thickness of the negative active material layer.
3. The negative electrode according to claim 1, wherein The silicon layer has a thickness of 10 μm to 85 μm.
4. The negative electrode according to claim 1, wherein The first crystalline carbon layer has a thickness of 10 μm to 120 μm.
5. The negative electrode according to claim 1, wherein The second crystalline carbon layer has a thickness of 10 μm to 120 μm.
6. The negative electrode according to claim 1, wherein The first crystalline carbon layer and the second crystalline carbon layer each include artificial graphite, natural graphite, or a mixture thereof.
7. The negative electrode according to claim 1, wherein The silicon layer also includes crystalline carbon.
8. The negative electrode according to claim 7, wherein The silicon layer includes the Si-carbon composite and the crystalline carbon in a weight ratio of 9:91 to 60:
40.
9. The negative electrode according to claim 1, wherein The Si-carbon composite includes silicon nanoparticles and amorphous carbon.
10. The negative electrode according to claim 1, wherein The Si-carbon composite includes secondary particles in which silicon primary particles are aggregated, and amorphous carbon is on the primary particles and the secondary particles.
11. The negative electrode according to claim 9, wherein The Si-carbon composite also includes crystalline carbon.
12. The negative electrode according to claim 10, wherein The secondary particles also include crystalline carbon.
13. A rechargeable lithium battery, comprising: The negative electrode according to any one of claims 1 to 12; A positive electrode, including a positive active material; as well as Non-aqueous electrolyte.